Augmented island topographies - Annual Conference 2022 - Medialities (Conference Medialities 2022, 2022)
The third annual conference of the Africa Multiple Cluster of Excellence takes place in Bayreuth and Makhanda (ACC Rhodes) from 6 to 9 July 2022. It is dedicated to the annual theme of Medialities and completes the thematic work of the previous academic year. As one of the four "heuristics" around which the cluster organises its collective theoretical and conceptual work, the topic Medialities serves as a guide for exploring the Cluster's core concepts. The conference offers members of the Africa Multiple Cluster of Excellence a forum to present and discuss their latest research in the thematic field of Medialities in self-organised groups (panels). The conference thus creates a space for theoretical debates and intellectual exchange among members of the Cluster - including the African Cluster Centres at Moi University (Kenya), Rhodes University (South Africa), Joseph Ki-Zerbo University (Burkina Faso) and the University of Lagos (Nigeria). It will be held in a hybrid format to facilitate as much intercontinental exchange as possible. The conference programme features 3 keynote lectures 14 parallel thematic panel sessions 2 roundtable discussions 2 film screenings an artist event and a knowledge slam https://www.africamultiple.uni-bayreuth.de/en/index.html